The Urgency of Interactive Media in Improving Istima' Skills (Listening) in Arabic Language Learning: Systematic Literature Review - Marajo Marajo; Abderrazzaq Massouri (El-Syaker : Samarinda International Journal of Language Studies, 2026)
Proficiency istima' (listening skills) is a core ability in learning Arabic, but it often faces obstacles due to conventional learning methods. This study aims to evaluate the urgency of interactive technology in improving istima' skills through the Systematic Literature Review (SLR) approach. The analysis was conducted on 10 articles that met the inclusion criteria, including studies on interactive media such as YouTube, audio-visual platforms, multimedia-based applications, and e-learning. The results of the study show that interactive technology provides significant benefits, such as improving motivation, personalization of learning, and listening skills through a contextual and collaborative learning environment. Additionally, the technology supports students accessing materials flexibly and independently, allowing for a more effective learning experience. However, the effectiveness of the implementation of this technology is influenced by the supporting infrastructure and appropriate learning design. This study concludes that interactive technology is a complement and an essential element in istima' learning in the digital era. This study concludes that interactive technology is a complement and an essential element in istima' learning in the digital era.